THE DIVERSITY OF BIRDS AND ATTRACTIVE BIRDS AS AVITOURISM OBJECTS IN GUNUNG BROMO UNIVERSITY FOREST, KARANGANYAR, CENTRAL JAVA - Aditya Aditya; Sugiyarto Sugiyarto; Sunarto Sunarto; Galuh Masyithoh; Ike Nurjuita Nayasilana (ZOO INDONESIA, 2020)
The Gunung Bromo University Forest is a former tourism area which must be revitalized, one of them is to be an avitourism object. However, the information of birds diversity is still lacking. The research aimed to determine bird diversity and attractive birds as avitourism object in Gunung Bromo University Forest. The bird observation was con-ducted using the encounter rates method in six line transects. The quantitative and qualitative descriptive analysis was used to describe bird diversity and attractive birds as avitourism objects. The research resulted 44 species of birds belong to 26 families were found in the area. The diversity of birds belongs to moderate category with Shannon-Wiener Index of 2.75. The relative abundance of birds were categorized into one species of abundant, seven species of common, eight species of frequent, and 28 species of uncommon. Attractive birds in Gunung Bromo University Forest as avitourism object were three species of raptor, six species of endemic birds, five species of high conservation value birds, and other attractive birds such as colorful birds and songbirds. The bird community in Gunung Bromo University Forest has the potential as an object of avitourism with some opportunities and obstacles.